2013
DOI: 10.1111/zsc.12028
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity, intraspecific phenetic plasticity and recent geographical translocations inBranchiomma(Sabellidae, Annelida)

Abstract: The importance of identifying biological diversity accurately and efficiently is becoming more evident. It is therefore critical to determine the species boundaries between closely related taxa and to establish diagnostic characters that allow us to define species. This is not an easy task when species exhibit high intraspecific phenotypic plasticity or when distinct evolutionary lineages with an unusually large amount of genetic distinctiveness show no apparent morphological diversity (cryptic species). These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 96 publications
1
43
0
1
Order By: Relevance
“…This species was characterised and defined by molecular markers as Branchiomma sp. D (in Capa et al 2013). Some of the diagnostic morphological features of this species are the presence of a posterior peristomial ring collar with wide separated dorsal margins, the digitiform stylodes along radioles, with one or two pairs that are about twice as long as their neighbours and flattened and thoracic uncini with two rows of small teeth over the main fang.…”
Section: Bispira Serratamentioning
confidence: 99%
See 2 more Smart Citations
“…This species was characterised and defined by molecular markers as Branchiomma sp. D (in Capa et al 2013). Some of the diagnostic morphological features of this species are the presence of a posterior peristomial ring collar with wide separated dorsal margins, the digitiform stylodes along radioles, with one or two pairs that are about twice as long as their neighbours and flattened and thoracic uncini with two rows of small teeth over the main fang.…”
Section: Bispira Serratamentioning
confidence: 99%
“…Branchiomma bairdi is distinguished from other congeners by the presence of strap-like and long macrostylodes (up to four times the length of the neighbouring digitiform stylodes, not so large in small specimens), and the colour pattern, with olive-green bodies and conspicuous bright orange spots alternating with radiolar eyes. This species was originally described from the Caribbean but has recently been reported is other biogeographical areas as an invasive species (Tovar-Hernández et al 2009Arias et al 2013;Capa et al 2013;Capa 2014). First record from Lizard Island.…”
Section: Bispira Serratamentioning
confidence: 99%
See 1 more Smart Citation
“…Some widespread polychaetes are being shown to represent suites of cryptic species (Carlton 2009;Capa et al 2013). For example, some current work on nereidids has shown that using both morphological and molecular data to redefine species boundaries considerably reduces the distributional ranges (Glasby et al 2013).…”
Section: Regional Biogeographic Comparisonmentioning
confidence: 99%
“…While polychaete collections were historically preserved in formalin, contemporary collection practice now routinely preserves material in ethanol to enable subsequent genetic studies, which are changing our taxonomic concepts -see for example Capa et al (2010Capa et al ( , 2013 and Wei et al (2013). Such studies are expected to continue and the contemporary surveys underway (2009)(2010)(2011)(2012)(2013)(2014) in the Project Area are undertaking such practices.…”
Section: Future Directionsmentioning
confidence: 99%